Aging dysregulates neutrophil extracellular trap formation in response to HIV in blood and genital tissues - Moreno de Lara, Laura; Werner, Alexandra; Borchers, Anna; Carrillo-Salinas, Francisco J.; Marmol, Wendelin; Parthasarathy, Siddharth; Iyer, Vidya; Vogell, Alison; Illanes, Diego; Abadía-Molina, Ana C.; Ochsenbauer, Christina; Wira, Charles R.; et al. (Frontiers in Immunology, 2023)
Women acquire HIV through sexual transmission, with increasing incidence in women >50 years old. Identifying protective mechanisms in the female genital tract (FGT) is important to prevent HIV-acquisition in women as they age. Human genital and blood neutrophils inactivate HIV by releasing neutrophil extracellular traps (NETs), an innate protective mechanism against HIVinfection. However, how NET formation is triggered by HIV in different tissues and whether this mechanism is affected by aging remain unknown. We demonstrate that the mechanisms that trigger NET release in response to HIV are different in blood and genital tissues, and that NET release decreases with aging. In blood neutrophils, HIV stimulation independently activated calcium pathways and endosomal TLR8, but aging reduced calcium responses, resulting in delayed NET release. In contrast, calcium responses were absent in genital neutrophils and NET release was triggered preferentially through TLR8 activation, but aging impaired this pathway. HIV induced 2 NET formation through non-lytic pathways in blood and FGT neutrophils, except for a small subset of NETs that incorporated annexin V and lactoferrin predominantly in blood, suggesting proinflammatory and lytic NET release. Our findings demonstrate that blood neutrophils cannot model genital neutrophil responses which has important implications to understanding protection against HIV acquisition.